DYNAMICS THE ZONATION POLICY SYSTEM FOR UPPER SECONDARY STUDENT ADMISSIONS IN KAMPAR DISTRICT RIAU PROVINCE - Nurman, Nurman; Kumalasari, Eka; Erlina, Erlina; Yuli, Annisa Rahma (CosmoGov: Jurnal Ilmu Pemerintahan, 2024)
The development of information technology has entered various fields. Utilization of information and telecommunications technology in public services. It is no longer something new for developed countries. Apart from that, there is demand from the public for information which requires the Government to provide public services that suit the needs of the community. Policy implementation is one of the stages of public policy, between policy formation and the policy consequences for the communities it influences. If a policy is inappropriate or cannot reduce the problem that is the target of the policy, then the policy will probably fail even if the policy is implemented very well. Meanwhile, a policy that has been planned very well may also fail if the policy is not implemented well by the policy implementers. The aim of this research is to determine the Policy Dynamics of the Zoning System for Admission of High School Students in Kampar Regency, Riau Province. This research uses a qualitative method with stages including preparing a research design, determining the location and research informants, collecting data, analyzing data, presenting data and drawing conclusions. Research findings show that the school and local government cannot confirm zoning boundaries so that prospective new students cannot register and fail to enter the nearest school even though they are in the zone and end up enrolling in private schools which require a lot of education costs.gb777